APLIKASI TEKNIK SPHERIFICATION PADA COATING SARI BUAH JERUK - Indah Yuliasih, Sugiarto, dan Melisa Constantia (Jurnal Teknologi Industri Pertanian, 2017)
Fruit extract coating is an innovative food product which created by spherification technique involved adding a small quantity of sodium alginate into a fruit extract and carefully dropping this liquid into calcium chloride solution. The fruit extract came in contact with the calcium chloride solution created a sphere. The objectives of this research were to find the best formulation of sodium alginate (0.6, 0.7, and 0.8%), calcium chloride (0.6 and 0.7%), and glucose solution (15 and 22.5 obrix) for producing orange extract coating, and to analyze their characteristics.  The best formula based on consumer hedonic test was 0.8% sodium alginate, 0.7% calcium chloride, and 15 obrix  glucose solution. In this formula, orange extrac coating had total acid of 112 mg/100 g, 6.56% total glucose, 48.4 mg/100 g vitamin C, and total suspended solids of 1033.33 mg/L.Keywords: orange extract coating, spherification,  sodium alginat and calcium chloride